Boost Zakat Fundraising Through E-Customer Relationship Management in Digital Era - Doddy, Muhammad; Ali, Juhary; Hindardjo, Anton; Sani, Asrul (Technium Business and Management, 2022)
At present, zakat payments allow payment via online. Therefore, the relationship between the Amil Zakat Institution and the muzakki must be strengthened, primarily through online zakat payments. E-CRM or what is known as e-Customer Relationship Management is used to facilitate the implementation of CRM in the world of digital payments. E-CRM allows the Amil Zakat Institution to provide appropriate services to satisfy muzakki and increase muzakki loyalty in paying zakat through online applications. Also, the E-CRM feature is essential for management. Zakat Payer Relations Online, without the e-CRM feature, CRM in the world of online zakat payments cannot be realized. Some literature there is no theoretical model for E-CRM implementation on online zakat payments. Besides, there are shortcomings in previous studies that focused on identifying the importance and categorization of e-CRM features in the various stages of the transaction cycle. So, this study seeks to fill the information gap based on empirical data obtained from the survey. The purpose of this study is to examine the relationship between E-CRM features in online zakat payments and online zakat payer loyalty at various stages of the pre-payment, when-payment, and post-payment transaction cycle. The results of this study indicate that the use of E-CRM in online zakat payment applications can affect the satisfaction and loyalty of online zakat payers. Research contributes to the role of the E-CRM feature in increasing the loyalty of zakat payers online at various stages of the payment cycle. What’s more, this study highlights the critical elements of the E-CRM program, where online zakat payment applications must invest to increase the loyalty of zakat payers.